High‐Performance Perovskite Solar Cells with Enhanced Environmental Stability Based on a (p‐FC6H4C2H4NH3)2[PbI4] Capping Layer. Issue 12 (5th February 2019) - Zhou, Qin; Liang, Lusheng; Hu, Junjie; Cao, Bingbing; Yang, Longkai; Wu, Tingjun; Li, Xin; Zhang, Bao; Gao, Peng
Abstract: Supported by the density functional theory (DFT) calculations, for the first time, a fluorinated aromatic cation, 2‐(4‐fluorophenyl)ethyl ammonium iodide (FPEAI), is introduced to grow in situ a low dimensional perovskite layer atop 3D perovskite film with excess PbI2 . The resulted ( p ‐FC6 H4 C2 H4 NH3 )2 [PbI4 ] perovskite functions as a protective capping layer to protect the 3D perovskite from moisture. In the meantime, the thin layer facilitates charge transfer at the interfaces, thereby reducing the nonradiative recombination pathways. Laser scanning confocal microscopy unveils visually the distribution of the 2D perovskite layer on top of the 3D perovskite. When employing the 3D–2D perovskite as the absorbing layer in the photovoltaic cells, a high power conversion efficiency of 20.54% is realized. Superior device performance and moisture stability are observed with the modified perovskite over the whole stability test period. Abstract : Fluorinated aromatic cations (FPEAI) can react with the excess PbI2 in a 3D perovskite film to form a capping 2D perovskite layer. Compared to the control device, the resulting multidimensional perovskite shows enhanced environmental stability with equally superior device performances. Judicious optimization of the perovskite precursor recipe realizes a power conversion efficiency of 20.54% for mesoporous perovskite solar cells.